2016
DOI: 10.1016/j.ces.2016.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of particle size and shape properties on cake resistance and compressibility during pressure filtration

Abstract: International audienceThe aim of this paper was to study cake filterability and compressibility as a function of the particle shape and particle size distribution (PSD). Different shapes and PSD of calcium carbonate and uranium oxalate particles covering the classical types encountered in industry (sphere, cube, needle and platelet) were obtained by precipitation. The size and shape factor distributions were measured using an image analysis system on SEM pictures. The cake filtration properties were measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(48 citation statements)
references
References 17 publications
2
36
0
1
Order By: Relevance
“…In order to achieve a high packing density, a wide particle size distribution of smooth spherical particles is generally considered . Bourcier et al reported that particle size caused great impacts on packing resistance during pressure filtration (shape factor was of secondary importance); a smaller particle size led to a higher packing resistance and a longer filtration time.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve a high packing density, a wide particle size distribution of smooth spherical particles is generally considered . Bourcier et al reported that particle size caused great impacts on packing resistance during pressure filtration (shape factor was of secondary importance); a smaller particle size led to a higher packing resistance and a longer filtration time.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to consider the mechanical properties of specific solid particles, along with their shape and size distributions, to adequately describe the behavior of the respective cake and the separation characteristics. Several authors have investigated the influence of these parameters and other factors on cake filtration, e.g., solid‐liquid interactions and suspension stability over time , filter testing method , and operating pressure .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the detailed knowledge of the Particle Size Distribution (PSD) and Particle Size and Shape Distribution (PSSD) becomes an issue of extreme relevance when developing materials with advanced functionalities. This is for example the case of electroluminescent perovskites 9 , heterogeneous catalysts 10 , nanomaterials for optoelectronics 11 , photovoltaics 12 , drug delivery 13 , or in industrially relevant processes, such as filtration 14 , coating 15 , dyes and inks 16 , cosmetics 17 and active pharmaceutical ingredients formulation 18 .…”
Section: Introductionmentioning
confidence: 99%